2017
DOI: 10.1105/tpc.17.00309
|View full text |Cite
|
Sign up to set email alerts
|

Two Complementary Mechanisms Underpin Cell Wall Patterning during Xylem Vessel Development

Abstract: The evolution of the plant vasculature was essential for the emergence of terrestrial life. Xylem vessels are solutetransporting elements in the vasculature that possess secondary wall thickenings deposited in intricate patterns. Evenly dispersed microtubule (MT) bands support the formation of these wall thickenings, but how the MTs direct cell wall synthesis during this process remains largely unknown. Cellulose is the major secondary wall constituent and is synthesized by plasma membrane-localized cellulose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 52 publications
3
86
0
Order By: Relevance
“…Imaging of the fluorescence protein-tagged Arabidopsis secondary wall CESA7 revealed that clusters of CESA complexes moved in the same direction along the cortical microtubule tracks in Arabidopsis epidermal cells induced to undergo transdifferentiation into xylem cells, leading to the suggestion that the coalescence of cellulose microfibrils into macrofibrils in secondary walls is attributed to the clustering of CESA complexes (Watanabe et al, 2015;Li et al, 2016). The alignment of CESAs with the underlying cortical microtubules is mediated by CSI1, a cellulose synthase-interactive protein, which was first discovered as a link between primary wall CESAs and cortical microtubules and subsequently shown to be required for the alignment of secondary wall CESAs with cortical microtubules during the early phase of xylem secondary wall thickening (Li et al, 2015;Schneider et al, 2017). CSI1 was recently found to guide the docking of the CESA complex-containing vesicles to specific plasma membrane domains through its interaction with microtubules (Zhu et al, 2018).…”
Section: Cellulose Synthase Activity and Cellulose Microfibril Deposimentioning
confidence: 99%
“…Imaging of the fluorescence protein-tagged Arabidopsis secondary wall CESA7 revealed that clusters of CESA complexes moved in the same direction along the cortical microtubule tracks in Arabidopsis epidermal cells induced to undergo transdifferentiation into xylem cells, leading to the suggestion that the coalescence of cellulose microfibrils into macrofibrils in secondary walls is attributed to the clustering of CESA complexes (Watanabe et al, 2015;Li et al, 2016). The alignment of CESAs with the underlying cortical microtubules is mediated by CSI1, a cellulose synthase-interactive protein, which was first discovered as a link between primary wall CESAs and cortical microtubules and subsequently shown to be required for the alignment of secondary wall CESAs with cortical microtubules during the early phase of xylem secondary wall thickening (Li et al, 2015;Schneider et al, 2017). CSI1 was recently found to guide the docking of the CESA complex-containing vesicles to specific plasma membrane domains through its interaction with microtubules (Zhu et al, 2018).…”
Section: Cellulose Synthase Activity and Cellulose Microfibril Deposimentioning
confidence: 99%
“…The 360 parameters that normally distinguish between these regimes then control only the thickness of the bands. This means that the relatively thick active ROP bands that would be needed to generate the relatively thin microtubule bands observed in protoxylem patterning [10] may actually originate from a Turing mech-365 anism that would generate gaps without diffusion restriction. Additionally, the finding that diffusion restriction can essentially turn spot, stripe, and gap regimes into one large band regime may imply an increased robustness of the protoxylem pattern to changes in ROP activity.…”
Section: Directional Diffusion Restriction Can Orient Rop Patterns Inmentioning
confidence: 99%
“…This robustness of straight patterns has several benefits for the biological system. Firstly, in order to create the actual cell 415 wall pattern, the underlying ROP and microtubule patterns will need to remain approximately stationary for the duration of secondary cell wall synthesis, which may take many hours [10], so the ROP pattern should be robust to any perturbations that may occur in this time frame. Secondly, due to the difficulty of re-420 orienting a pattern of oblique bands, it seems important that the reorientation of the microtubule array to a transverse state occurs before the start of ROP patterning.…”
Section: Fully Formed Banded Patterns Are Relatively Robust Struc-mentioning
confidence: 99%
See 1 more Smart Citation
“…CELLULOSESYNTHASE INTERACTING PROTEIN1 (CSI1), also known as POM-POM2 (POM2), interacts with CesAs and has been suggested to act as a scaffold mediating their movement along the microtubules (Gu and Somerville, 2010;Bringmann et al, 2012;Li et al, 2012). New work from Schneider et al (2017) provides evidence that microtubules and CSI1/POM2 function early in secondary wall deposition but are not required for later stages of secondary wall development.…”
mentioning
confidence: 99%